Characteristics of Wellens’ Syndrome in the Current PCI Era: A Single-Center Retrospective Study - Li Zhou; Xuhe Gong; Hui Chen; Tianhui Dong; He-he Cui; Hongwei Li (Emergency Medicine International, 2023)
Objectives. The goal of this retrospective study was to reveal the prevalence, angiographic characteristics, clinical presentation, and long-term outcomes of non-ST-segment elevation myocardial infarction (NSTEMI) patients with Wellens’ syndrome. Background. Procedural results for percutaneous coronary intervention (PCI) in acute coronary syndrome (ACS) have improved in recent years. However, there is still a paucity of available clinical trial data for Wellens’ syndrome even though it is a well-known high-risk ACS. Methods. Among a total of 3528 patients with ACS who underwent angioplasty from 2017 to 2019 at the Cardiovascular Center of Beijing Friendship Hospital, 476 NSTEMI patients with culprit left anterior descending (LAD) vessels were enrolled in this study. According to electrocardiographic criteria of Wellens’ syndrome, the patients were divided into a Wellens group (n = 138) and a non-Wellens group (n = 338). The primary endpoint was cardiac death; the secondary endpoints were main adverse cardiovascular and cerebrovascular events (MACCEs), a composite of all-cause death, cardiac death, heart failure, target lesion revascularization, recurrent myocardial infarction, and stroke. All of the medical and follow-up data were obtained from our institutional database. Results. The incidence of Wellens’ syndrome in all ACS patients was 5.7% (200 of 3528). Among the 200 patients with Wellens’ syndrome, 138 had NSTEMI, for a proportion of 69%. There was a significant decrease in the percentage of preexisting coronary heart disease (CHD), prior myocardial infarction, and previous PCI (P<0.05) in the Wellens group compared with the non-Wellens group. On coronary angiography, single-vessel lesions were more common in the Wellens group (11.6% vs. 5.3%, P=0.016), and almost all (97.1%) of these patients received drug-eluting stents. Notably, the Wellens group had a higher proportion of early PCI than the non-Wellens group (71% vs. 61.2%, P=0.044). At 24 months, there was no statistically significant difference in cardiac death (P=0.111) between the two groups, but the MACCEs were comparable (Wellens: 5.1% vs. non-Wellens: 13.3%, P=0.009). Age ≥65 years was the largest independent risk factor for adverse prognosis. Conclusions. With early recognition and aggressive intervention, Wellens’ syndrome is no longer a risk factor for adverse prognosis in patients with NSTEMI in the current PCI era.